2013
DOI: 10.1111/jgs.12317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Person‐Centered Mouth Care Intervention on Care Processes and Outcomes in Three Nursing Homes

Abstract: As little as 8 weeks of mouth care can significantly improve oral hygiene outcomes. Given the consequences of poor oral hygiene, greater attention to mouth care education and provision are merited. The dedicated worker model is controversial, and future work should assess whether other models of care are equally beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 26 publications
2
89
0
1
Order By: Relevance
“…Germany requires that at least 50% of all care staff are Registered Nurses who have had 3-year geriatric training [76]. Considering the significant role of workforce in healthcare delivery [77] and the influence of workforce training on resident outcomes and staff working experiences [14,78], the sub-optimal staff qualification in Chinese NHs suggests this is a critical area for policy development to improve the capacity of Chinese NHs to provide competent and safe care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germany requires that at least 50% of all care staff are Registered Nurses who have had 3-year geriatric training [76]. Considering the significant role of workforce in healthcare delivery [77] and the influence of workforce training on resident outcomes and staff working experiences [14,78], the sub-optimal staff qualification in Chinese NHs suggests this is a critical area for policy development to improve the capacity of Chinese NHs to provide competent and safe care.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of NH staff have been extensively researched in other countries in studies of staff demographics and educational preparation and how these characteristics influence resident outcomes in NHs. For example, an interventional study in 3 NHs in the U. S. found that resident oral health was improved after training certified nurse aide about mouth care [14]. A qualitative study about end-of-life care in NHs in UK found that staff expertise about end-of-life care and their strong relationships with residents facilitated end-of-life care for residents with dementia [15].…”
Section: Introductionmentioning
confidence: 98%
“…As described by Brownie [18], the concept and philosophy of person-centred care has been well described, developed and refined through conceptual work, and a number of studies have explored a variety of interventions with different endpoints [18]. Some interventions have been related to specific care situations such as bathing, mouth care or morning care [1921], and others have focused on developing the physical environment to meet the needs of people with dementia [22, 23]. A few intervention studies have had a multi-dimensional, holistic, and individually tailored approach [24, 25], or been part of the conceptual development of person-centred care for example through life story work [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…We included a total of seven references [65, 66, 91–95], four of which report different aspects of one unique research project [66, 9294]. Therefore, these seven references represent four unique studies (i.e., research projects).…”
Section: Resultsmentioning
confidence: 99%
“…However, evidence on the effectiveness of these strategies is weak or inconclusive, and these strategies have not been tested in the context of daily oral care. A few specific strategies to reduce responsive behaviors during oral care have been suggested and trialed [65, 66] but to date, no systematic review on the effectiveness of such strategies is available.…”
Section: Introductionmentioning
confidence: 99%